The creative thinking handbook - Griffiths, Chris (Kogan Page Ltd, 2019)
Thinking about your thinking -- The decision radar -- Common thinking errors: selective thinking -- Common thinking errors: reactive thinking -- Common thinking errors: assumptive thinking -- The solution finder -- The context for creative problem solving -- The solution finder step 1: Understanding -- The solution finder step 2: Ideation -- The solution finder step 2: Ideation toolkit -- The solution finder step 3: Analysis -- The solution finder step 4: Direction -- The end of the beginning -- Commit to "thinking differently" -- Creative leadership -- Conclusion: where do you go from here?.